Carbon capture capacity of the palmera datilera Phoenix Dactylifera as an environmental service in the district of Tacna - Loyola Cabana, Fernando Edward (2019)
In recent years, the car park in Tacna’ city has increased, as well as the emission of polluting gases such as carbon dioxide (CO2) generated by different types of vehicles, mainly those of public transport in the city of Tacna. The research work was aimed at determining the carbon capture as an environmental service through the palm trees that are in the Bolognesi avenue, Industrial avenue and surroundings. For this purpose, the document Identification of existing methodologies to determine carbon stock in forest ecosystems of the Environment’s Ministry (MINAM) was used. Carbon estimation in tree biomass was chosen using the non - destructive - direct method, which consists of estimating of the biomass with dasometric data which were taken in the field. The study was carried out between June and October of 2016, in which two strata of palm trees were determined that are exposed to atmospheric CO 2 emissions from light vehicles, establishing eight sampling points for zone, in which, took a total of 16 samples. Samples were analyzed during the months after October, when data collection was completed. The results were as follows: zone 1 located around Bolognesi avenue with 637 specimens of Phoenix dactylifera had a content of 136,87 Tn CO2e and for zone 2 located around Industrial avenue with 369 specimens of Phoenix dactylifera had a content of 18,35 Tn CO2e, where zone 1 would have the largest amount of CO2 stored due to having about 60% of the total population of the individuals. Finally, it can be verified that the carbon capture capacity (CO2) of the Phoenix dactylifera acts as an environmental service in the district of Tacna, contributing positively to air quality, as a fundamental condition for the development of plant life And as mitigation to climate change by emissions of CO2 as a greenhouse gas, which comes from the car park of Tacna.